Evaluation and Determination of the Antioxidant Capacity of the Crude Extracts of Some Medicinal Plants - Hassan B. Yesufu; Ibrahim Iliya; Fanna I. Abdulrahman (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
The antioxidant properties of ten (10) plant species from various Nigerian states were assessed utilising the DPPH, H2O2, and FRAP test techniques . In the DPPH assay, Piliostigma reticulatum exhibited the best scavenging property at the lowest concentration (6.25 g/ml), whereas C. accuminata exhibited the best scavenging property at the greatest concentration (100 g/ml) . The following is the trend at the lowest concentration:; P. reticulatum> A. digitata> T. indica> C. accuminata> V. paradoxa> B. diezelli> S. longipediculata> A. squamosa> P. biglobosa> S. singueana. While the trend at the highest concentration is as follows; C. accuminata> B. diezelli> T. indica> P. biglobosa> A. digitata> V. paradoxa> A. squamosa> P. reticulatum> S. longipediculata> S. singueana. The H2O2 experiment revealed that B diezelli had the best scavenging ability at both the lowest (6.25) and highest concentrations (100).In addition, the following is the current trend:; B. diezelli> A. squamosa> S. longipediculata> S. singueana> V. paradoxa> P. bigloosa> C. accuminata> A. digitata> T. indica> P. reticulatum at the least concentration. While at the highest, the trend is as follows; B. diezelli>S. longipediculata> S. singueana> V. paradoxa> P. biglobosa> P. reticulatum> C. accuminata> A. digitata> T. indica. According to the FRAP assay, S. longipediculata had the most scavenging activity at the lowest concentration (6.25) while C. accuminata had the highest activity at the highest concentration. The following is the trend at the lowest concentration:; S. longipediculata> C. accuminata> T. indica> A. digitata> V. paradoxa> A. squamosa> P. reticulatum> P. biglobosa> S. singueana> B. diezelli. While at the highest concentration the trend is; C. accuminata> S. longipediculata> T. indica> A. digitata> A. squamosa> V. paradoxa> P. reticulatum> P. biglobosa> S. singueana> B. diezelli. In the FRAP assay, five (5) crude extracts (S. longepedicunlata, T. indica, A. digitata, A. squamosa, C. accuminata) were more active than the standard drug (ascorbic acid and butylated hydroxyl anisole) at higher concentrations. The methanol crude extract of Piliostigma reticulatum was more active in the DPPH assay than all other plants material. Annona squamosa and Parkia biglobosa methanol crude extracts were most active than the other extracts in the hydrogen peroxide assay.